2016
DOI: 10.1186/s12889-016-3271-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a novel two-desk sit-to-stand workplace (ACTIVE OFFICE) on sitting time, performance and physiological parameters: protocol for a randomized control trial

Abstract: BackgroundProlonged sitting is ubiquitous in modern society and linked to several diseases. Height-adjustable desks are being used to decrease worksite based sitting time (ST). Single-desk sit-to-stand workplaces exhibit small ST reduction potential and short-term loss in performance. The aim of this paper is to report the study design and methodology of an ACTIVE OFFICE trial.DesignThe study was a 1-year three-arm, randomized controlled trial in 18 healthy Austrian office workers. Allocation was done via a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…The study protocol ( Figure 2) -based on the one proposed by Schwartz and colleagues (Schwartz et al 2016) -comprised of a preparation phase, followed by five repeated trials of a test battery (described below) that assessed: reaction time [digital Stroop test, (Stroop 1935)], working speed (text editing task, self-developed see Appendix 1) and attention [d2R-test of attention, (Brickenkamp, Schmidt-Atzert, and Liepmann 2010)]. The measurement day concluded with a closing questionnaire.…”
Section: Study Protocolmentioning
confidence: 99%
“…The study protocol ( Figure 2) -based on the one proposed by Schwartz and colleagues (Schwartz et al 2016) -comprised of a preparation phase, followed by five repeated trials of a test battery (described below) that assessed: reaction time [digital Stroop test, (Stroop 1935)], working speed (text editing task, self-developed see Appendix 1) and attention [d2R-test of attention, (Brickenkamp, Schmidt-Atzert, and Liepmann 2010)]. The measurement day concluded with a closing questionnaire.…”
Section: Study Protocolmentioning
confidence: 99%
“…In this two-arm, randomised controlled cross-sover trial, 18 office workers randomly recruited via e-mail by regional health insurance were randomly allocated to either an intervention arm (study arm I) or a control arm (study arm II) by means of a covariate adaptive randomisation (Kang, Ragan, and Park 2008). Details of the study design can be found in Schwartz et al (2016). According to the cross-over design of this study, arm I participants were randomly allocated to two different subgroups (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The study was approved by the Ethics Committee of the University of Vienna (Reference number: 00052) and was registered at ClinicalTrials.gov (Identifier: NCT02825303, July 2016). A detailed description of the study protocol (exclusion and inclusion criteria, sample size calculations and screening) was previously published (Schwartz et al 2016).…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations